Digital Connectivity Bridging Digital ASEAN - Chong, Mei Teing; Puah, Chin Hong; Shazali, Abu Mansor; Teh, Chee Siong (2022)
The world is changing rapidly with the adoption of sophisticated digital technology. The foremost tool for digital technology operation is digital connectivity infrastructure. To unleash the potential of the digital economy in ASEAN countries, the foundation is upgrading its digital connection, which is a key part of making digitalization feasible. This study identified five factors that contributed to the digital connectivity of ten ASEAN countries and used them to calculate the overall score of each country to show its performance in terms of digital connectivity. The competitive analysis results of the five digital connectivity enablers in each country show their respective strengths and shortcomings. Myanmar made the greatest progress in overall digital connectivity, due to its engaging in national regulatory reforms and focusing connectivity developments after realizing the need to improve their ICT infrastructure. There is still much room for improvement in the network performance of ASEAN countries; among all ten countries, only Singapore has reached a very satisfactory level. Striving to narrow the digital connectivity development gap would be an important agenda item for all ASEAN countries.